How to Sell a Haunted House - Hendrix, Grady (New York : Berkley, 2023)
"New York Times bestselling author Grady Hendrix takes on the haunted house in a hilarious and terrifying new novel that explores the way your past-and your family-can haunt you like nothing else.... Louises parents have passed away, and shes returning to the small Southern town where she grew up to get their house ready to sell. It means shell have to spend time with her younger brother-and their old grudges make that a terrifying prospect. But childhood hurts pale in comparison to the dangers posed by what still lives inside the house"--
Keywords: Parents -- Death; Fiction; Siblings -- Fiction; House selling -- Fiction; Haunted houses -- Fiction; Domestic fiction; Horror fiction; Novels; Fiction